Internet Commerce Managing Financial on the Internet - Chandra Wibowo Widhianto (The Winners, 2001)
Article explain how to business through internet which are web business clarification, strategy effect, how to make profit, and business electronic changes consist of criptografy, EDI, signature, digital notarisation, file, payment, and how to get succes in internet business.